Museum der Bildenden Künste Leipzig - Jahresheft 1997. - Guratzsch, Herwig; Hartleb, Renate; Küster, Ulf; Mehnert, Karl-Heinz; Sander, Dietulf; Museum der bildenden Künste, Leipzig (Leipzig : Museum der bildenden Künste, 1998)
Klinger, Max ; Schwind, Moritz Von ; Puder, Ulf ; Berlit, Rüdiger ; Firit, Günter ; Ebersbach, Wolfram ; Gille, Sighard ; Grützke, Johannes ; Heisig, Bernhard ; Hoch, Susann ; Hofer, Carl ; Horst-Schulze, Paul ; Kluge, Gustav ; Miller, Richarde ; Müller-Simon, Gerald ; Puder, Ulf ; Rosa, Salvator ; Salamoun, Jiri ; Semm, Will ; Stötzer, Werner ; Böttcher), Strawalde (Jürgen ; Triegel, Michael ; Weidanz, Gustav ; Winter, Fritz ; Zeniuk, Jerry ; Müller, Gerhart Kurt ; Klee, Paul ; Hausner, Xenia ; Rauch, Neo
Duits
boek